Stress‐strain concentrations in high‐rise structure elements and monotonic disintegration under the influence of environment contamination - Keras, Valerijus; Valys, Aurimas; Mockiene, Jūrate (Journal of Civil Engineering and Management, 2005)
Abundance of metal masts and towers, their aging require to pay attention to corrosion phenomena and their after‐affects. Special attention should be paid to the changes of structural elements strength and strain (induced by the environment aggressiveness) and to the phenomena of viability exhaustion of the whole system (dissipation). In these respects more premises for developing the second limit state formation are found first of all in separate mast elements and local chains, later in the whole structure.The article deals with the premises of developing chemical and electromagnetic contamination, its forecast and processes which could result from the above‐mentioned pollution; it also analyses the destructive processes due to the pollution interaction with the material of structural elements as well as the consequences of aggressive contamination. Attention is also paid to the effect of the stress‐strain concentrations around the corroded spots and their influence on the destruction evolution. Aukštų statinių elementų deformacijų koncentracijos bei monotoniškas irimas, veikiant aplinkos taršai Santrauka. Metalinių stiebų ir bokštų gausa bei jų senėjimas verčia skirti daugiau dėmesio jų korozijos apraiškoms ir pasekmėms. Ypač reikia atkreipti dėmesį į konstrukcijos elementų stiprumo bei deformatyvumo pokyčius ir visos sistemos gyvybingumo resursų išsekimo apraiškas (disipaciją), kurie sietini su aplinkos agresyvumu. Šiuo atžvilgiu daugiau prielaidų yra antrajam ribiniam būviui susidaryti ‐ iš pradžių tam tikruose stiebo konstrukcijos elementuose bei lokalinėse grandyse, vėliau ir visoje konstrukcijoje. Nagrinėjamos statinio aplinkos cheminės bei elektromagnetinės taršos susidarymo prielaidos ir jų prognozės, procesai, kuriuos gali sukelti teršalai, stiebo darbo imitacinis modeliavimas, taršos sąveikos su konstrukcijos elementų medžiaga sukelti destruktyvūs procesai, agresyvios taršos procesų padariniai. Pažymėta įtempimų ir deformacijų koncentracijų aplink pažaidas veiksnio reikšmė destrukcijų raidai. Raktiniai žodžiai: stiebai, ribinis būvis, stiprumas, deformacija, aplinka, agresyvumas, korozija, irimas, kinetika. First Published Online: 14 Oct 2010